2007
DOI: 10.1007/s00425-007-0666-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolate-specific effects of ultraviolet radiation on photosynthesis, growth and mycosporine-like amino acids in the microbial mat-forming cyanobacterium Microcoleus chthonoplastes

Abstract: Microcoleus chthonoplastes constitutes one of the dominant microorganisms in intertidal microbial mat communities. In the laboratory, the eVects of repeated daily exposure to ultraviolet radiation (16:8 light:dark cycle) was investigated in unicyanobacterial cultures isolated from three diVerent localities (Baltic Sea = WW6; North Sea = STO and Brittany = BRE). Photosynthesis and growth were measured in time series (12-15 days) while UV-absorbing mycosporine-like amino acids (MAAs) and cellular integrity were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 53 publications
(49 reference statements)
2
14
0
Order By: Relevance
“…These cells had a much higher cell-specific chl a content (Table 2) and adhered very easily to the bottom of the petri dish. Even though the present excitation wavelength of 470 nm is not optimal for Cyanobacteria, growth rates of C. chthonoplastes could be determined at low to intermediate abundances in particular for slow-growing isolates and at high excitation irradiances (Pattanaik et al 2008).…”
Section: Measuring Range and Detection Limitsmentioning
confidence: 93%
See 1 more Smart Citation
“…These cells had a much higher cell-specific chl a content (Table 2) and adhered very easily to the bottom of the petri dish. Even though the present excitation wavelength of 470 nm is not optimal for Cyanobacteria, growth rates of C. chthonoplastes could be determined at low to intermediate abundances in particular for slow-growing isolates and at high excitation irradiances (Pattanaik et al 2008).…”
Section: Measuring Range and Detection Limitsmentioning
confidence: 93%
“…In the context of ongoing population and species extinction due to anthropologic changes of ecosystems, the description of physiological niches is imperative to explain species occurrence (hindsight) and propagation or displacement (forecast). So far, the method of in vivo growth fluorometry has been successfully applied to Cyanobacteria (Garcia-Pichel et al 1998, Pattanaik et al 2008 …”
Section: Importance Of In Vivo Growth Ratesmentioning
confidence: 99%
“…It is found that enhanced UV-B can affect cyanobacterial growth, photosynthesis, pigments, and morphology, though different responses are observed in different species treated with different UV doses (Jiang and Qiu 2005;Wu et al 2005;Rath and Adhikary 2007;Pattanaik et al 2008). On the other hand, cyanobacteria are the oldest autotrophic inhabitants of the planet and have evolved efficient mechanisms to cope with the stress of UV exposure (Castenholz and Garcia-Pichel 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, inhibitory activity against in vitro (proteolytic and coagulating) or in vivo (hemorrhagic, edematogenic, and lethality) activities of B. jararacussu venom is being presented for the first time. in such unfavorable biotic and abiotic conditions, they synthesize a variety of molecules with different biological and pharmacological properties (Pattanaik et al 2008;Pereira et al 2009), but an antivenom effect has not been described before. The proteolytic, coagulant, and hemorrhagic activities of venoms are caused by proteases, called serine protease and metalloproteinases.…”
Section: Discussionmentioning
confidence: 99%
“…One of these strategies is the production of photoprotective molecules such as mycosporine-like amino acids (MMAs), scytonemim secreted by cyanobacteria and flavonoids secreted by plants (Pereira et al 2009). MAAs are the strongest UVR-absorbing compounds in nature (Pattanaik et al 2008;Carreto and Carignan 2011), and a molecule (called Prasiolin) with such activity has been isolated from Prasiola calophylla and its chemical structure elucidated (Hartmann et al 2016). The adhesive property of the genus Prasiola has been described before, demonstrating a potential biotechnological application (Pereira et al 2009), but no study related to the biological or pharmacological effects of P. crispa has been performed previously.…”
Section: Introductionmentioning
confidence: 99%